A SURVEY OF GOITER IN HAZARA DIVISION - ullah, Rizwan; Shah, S Humayun; Khan, J A; Khan, Mir Hassan; uddin, Salah; Suhhan, Fazle (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT A survey of goiter in Hazara Division was carried out from April, 1990 to March. 1991. Out of31045 persons surveyed, 5469 were found to have goiter, thus showing an overall prevalence of 17.6%. The prevalence rate was higher in rural population (24%) as compared to urban (5%). Male female ratio was about 1:1.5. Increased prevalence was observed between 26 and 35 years for males whereas for females it was more in the age group of 36 to 45 years.